Clinical Course and Outcome of Patients with SARS-CoV-2 Alpha Variant Infection Compared to Patients with SARS-CoV-2 Wild-Type Infection Admitted to the ICU - Jorge Garcia Borrega; Jan-Hendrik Naendrup; Katrin Heindel; Laura Hamacher; Eva Heger; Veronica Di Cristanziano; Antje-Christin Deppe; Fabian Dusse; Wolfgang Alois Wetsch; Dennis Alexander Eichenauer; Alexander Shimabukuro-Vornhagen; Boris Böll; et al. (Microorganisms, 2021)
The alpha variant of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is associated with higher transmissibility and possibly higher mortality compared with wild-type SARS-CoV-2. However, few data are available on the clinical course of infections with the alpha variant compared with wild-type SARS-CoV-2 in critically ill patients in intensive care units (ICUs). Therefore, we retrospectively analyzed patients admitted to our ICU due to SARS-CoV-2 Alpha variant infection and compared characteristics and course to patients with SARS-CoV-2 wild-type infection. The median age of patients with Alpha variant infections was 57 years compared to 62 years in the wild-type group. ICU survival was 41/80 (51%) in the Alpha variant group and 35/80 (44%) in the wild-type group (p = 0.429). Results of a matched-pair analysis based on age and sex illustrated that 45/58 patients (77.6%) in the Alpha variant group and 38/58 (65.5%) patients in the wild-type group required mechanical ventilation (p = 0.217). ICU survival was documented for 28/58 patients (48.3%) in the Alpha variant group and 27/58 patients (46.6%) in the wild-type group (p = 1). Thus, ICU mortality among patients with SARS-CoV-2 infections remains high. Although the Alpha variant group included younger patients requiring mechanical ventilation, no significant differences between patients with the SARS-CoV-2 Alpha variant and the SARS-CoV-2 wild-type, respectively, were detected with respect to clinical course and ICU mortality. For future VOCs, we believe it would be important to obtain valid and rapid data on the clinical course of critically ill patients who test positive for COVID-19 in order to perform appropriate epidemiological planning of intensive care capacity.